ニホン スウェーデン コクサイ キョウドウ ダイキキュウ カンソク ホウコク - 鮎川, 勝; アユカワ, マサル; 江尻, 全機; エジリ, マサキ; Ayukawa, Masaru; Ejiri, Masaki (1981)
P(論文) 本報告は, 日本-スウェーデン国際共同大気球観測計画の初年度として, 日本製の大気球を初めて外国で使用して実施した大気球実験の経過と初期解析結果の報告である。1980年9月10日および11日に, オーロラ粒子の降り込みに伴うエネルギー収支の研究を目的とした大気球実験を, スウェーデン国キルナ市エスレンジ(67°52.2′N, 21°04.2′E)において実施した。実験は2機とも成功し, オーロラX線, VLF自然電波およびオゾン密度分布等のデータを収得した。また9月1日から約1ヵ月間, 同場所においてオーロラに伴う超高層物理現象の地上観測を行った。 This report is to describe a result of the first Japanese balloon campaign at Esrange (67°52.2′N, 21°04.2′E) which has been carried out in August-September, 1980. Two balloons of Japanese type B_5 (5000m^3) were successfully flown on September 10 and 11,1980 from the balloon launching pad at Esrange, Kiruna, Sweden. A prime objective in this campaign was to study the high-latitude (auroral zone) upper-atmospheric phenomena associated with magnetospheric/ionospheric activities. Also to establish technological basis for a first launching of Japanese balloons at Esrange was of prime importance in this campaign. Two balloons have been successfully flown and typical quiet time data of VLF waves, X-rays and ozone contents have been obtained. These are data bases for the study of high-latitude phenomena representing a quiet time condition. Since the launching itself depends on the weather and since the ceiling period is not very long due to the limitation of flight area (within Swedish territory) this time, it is very difficult to encounter a magnetic disturbance within a week of launching window. The ground-based observations of VLF waves, ULF waves, magnetic variations and cosmic noise absorptions have been carried out during the campaign of about one month. The first Japanese balloon campaign at Esrange has been hereby successfully completed. departmental bulletin paper